Identifying Oneself with the Face of Someone Else Impairs the Egocentered Visuo-spatial Mechanisms: A New Double Mirror Paradigm to Study Self–other Distinction and Interaction - Thirioux, Bérangère; Wehrmann, Moritz; Langbour, Nicolas; Jaafari, Nematollah; Berthoz, Alain (Frontiers in Psychology, 2016)
Looking at our face in a mirror is one of the strongest phenomenological experiences of the Self in which we need to identify the face as reflected in the mirror as belonging to us. Recent behavioural and neuroimaging studies reported that self-face identification not only relies upon visual-mnemonic representation of one’s own face but also upon continuous updating and integration of visuo-tactile signals. Therefore, bodily self-consciousness plays a major role in self-face identification, with respect to interplay between unisensory and multisensory processing. However, if previous studies demonstrated that the integration of multisensory body-related signals contributes to the visual processing of one’s own face, there is so far no data regarding how self-face identification, inversely, contributes to bodily self-consciousness. In the present study, we tested whether self-other face identification impacts either the egocentered or heterocentered visuo-spatial mechanisms that are core processes of bodily self-consciousness and sustain self-other distinction. For that, we developed a new paradigm, named “Double Mirror”. This paradigm, consisting of a semi-transparent double mirror and computer-controlled Light Emitting Diodes, elicits self-other face merging illusory effect in ecologically more valid conditions, i.e., when participants are physically facing each other and interacting. Self-face identification was manipulated by exposing pairs of participants to an Interpersonal Visual Stimulation in which the reflection of their faces merged in the mirror. Participants simultaneously performed visuo-spatial and mental own-body transformation tasks centered on their own face (egocentered) or the face of their partner (heterocentered) in the pre- and post-stimulation phase. We show that self-other face identification altered the egocentered visuo-spatial mechanisms. Heterocentered coding was preserved. Our data suggest that changes in self-face identification induced a bottom-up conflict between the current visual representation and the stored mnemonic representation of one’s own face which, in turn, top-down impacted bodily self-consciousness.